Motor vehicle insurance law: ignoring the lessons from King Rex - Ferris, Katy; Marson, James (Kluwer Law International, 2017)
Following a review in 2013, the Motor Insurers’ Bureau (MIB) established the Uninsured Drivers Agreement (UDA) 2015. The aim was to implement aspects of the Motor Vehicle Insurance Directives (MVID). The UDA 2015 contained numerous errors in its drafting and led to widespread criticism due to its incompatibility with EU law and common law principles. In January 2017 the MIB provided its Supplementary Uninsured Drivers Agreement. If its aim was to remedy these problems we argue that it has substantially failed. Further, the updated Agreement continues the uncertainty of the law in this area and, with reference to Fuller’s ‘Eight Ways to Fail to Make Law’, we present an argument that the Secretary of State for Transport should again redraft the UDA 2015 and the 2017 Supplement to provide legal certainty, remove the inconsistencies between national and EU law, and provide the protection to which third-party victims of uninsured drivers are entitled under EU law.